Thieno[2,3-b]thiophene based polymers: Synthesis and optoelectronic properties - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Synthesis of novel thieno[2,3-b]thiophenes (TTs) possessing para substituted phenyl groups (Ph-, MeOPh-, BrPh-, NO2Ph-, NH2Ph- and NMe2Ph-) at C-3 has been achieved through ring closure reactions of mono ketones, i.e. 1-aryl-2-(thiophen-2-ylthio)ethan-l-one, and polymerizations of TTs (PhTT (10), p-MeOPhTT (11), pNO(2) PhTT (13) and p-NMe2PhTT (18)) under Suzuki coupling condition are demonstrated. The optical and electronic properties of the polymers were investigated systematically. Polymers demonstrated bathochromic shift with respect to their monomers in UV-Vis investigations up to 203 nm for 23 consisting of NO2 unit. While unsubstituted phenyl possessing polymer has the smallest band gap of 2.18 eV, the largest one was noticed to be 2.65 eV for NMe2 containing polymer 24. Electrochemical studies revealed the relatively low oxidation potentials recorded between 1.10 and 1.31 V.
Keywords: Thieno[2,3-b]thiophene; Optoelectronic; UV-Vis; Cyclic voltammetry; Computation; THIN-FILM TRANSISTORS; SOLAR-CELLS; SENSING PROPERTIES; CHARGE-TRANSPORT; THIENOTHIOPHENE; COPOLYMERS; DITHIENOTHIOPHENES; SEMICONDUCTORS; THIOPHENE; UNITS